Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Ferrette, Bruno Lopes da Silva; Mourato, Bruno; Hazin, Fábio Hissa Vieira; Arocha, Freddy; Williams, Samuel Mackey; Rodrigues Junior, Carlos Egberto; Porto-Foresti, Fábio [UNESP]; de Amorim, Alberto Ferreira; Rotundo, Matheus Marcos; Coelho, Rui; Hoolihan, John P.; Sow, Fambaye Ngom; et al. (Springer Nature, 2021)
Since the Miocene profound climatic changes have influenced the biology and ecology of species worldwide, such as their connectivity, genetic population structure, and biogeography. The goal herein is to evaluate the phylogeography of sailfish Istiophorus platypterus between the Atlantic, Indian, and Pacific oceans. Our results evidenced a high genetic diversity and three distinct populations among the ocean basins with limited gene flow among them. In addition, the species is characterized by two deep evolutionary lineages that diverged during the Miocene/Pliocene transition, one of them is circumtropical while the other is restricted to the Atlantic Ocean. These lineages evolved along the successive glacial-interglacial cycles from the Pleistocene and remained isolated from each other in glacial refugium until deglaciation. Assessments of sailfish suggest it may be subject to overfishing and the results herein imply the need to re-evaluate the current stock delimitations and management measures adopted by the Regional Fisheries Management Organizations, especially in the Atlantic and the Indo-Western Pacific oceans to effectively manage the species. In addition, this work highlights that both lineages should at least be treated as two distinct management units in the Atlantic Ocean until their taxonomic status is fully resolved, given their high genetic divergence.
Keywords: Fisheries management units; Genetic population structure; Historical demography; Historical gene flow; Istiophorus platypterus; Mitochondrial DNA control region